2010
DOI: 10.5551/jat.3657
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Fish-Based Diet on the Serum Adiponectin Concentration in Young, Non-Obese, Healthy Japanese Subjects

Abstract: Aim: Adiponectin has insulin-sensitizing, anti-atherogenic, and anti-inflammatory properties, and researchers have recently reported that -3 polyunsaturated fatty acid (PUFA) can increase the serum adiponectin concentration, suggesting that dietary factors, such as fish intake, may have an influence on the serum adiponectin concentration. In general, Japanese subjects consume twice as much fish as people in other countries. We hypothesized that incremental change in serum -3 PUFA levels by fish intake is an im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 34 publications
0
28
2
Order By: Relevance
“…Despite existing data indicating increased adiponectin levels associated with omega-3 supplementation [61,62], no significant correlations were observed to plasma phospholipid levels of omega-3 or omega-6. Conversely, leptin was significantly positively associated with plasma phospholipid levels of alpha linoleic acid.…”
Section: Accepted M Manuscriptcontrasting
confidence: 68%
“…Despite existing data indicating increased adiponectin levels associated with omega-3 supplementation [61,62], no significant correlations were observed to plasma phospholipid levels of omega-3 or omega-6. Conversely, leptin was significantly positively associated with plasma phospholipid levels of alpha linoleic acid.…”
Section: Accepted M Manuscriptcontrasting
confidence: 68%
“…Epidemiological studies have shown that people consuming a Mediterranean diet tend to have a lower risk of developing cardiovascular diseases, diabetes, and cancer 13) . At the molecular level, the beneficial effects of consuming Mediterranean diet components are believed to be mediated at least in part by their positive modulation of adiponectin [14][15][16] ; however, it is unclear whether the linear relationship between a Mediterranean diet and adiponectin is sustained under the influence of the adiponectin-lowering effects of cigarette smoking and whether this relationship is independent of potential confounders in subjects adhering long term to a Mediterranean-style diet.…”
Section: Anthropometrics and Clinical Parametersmentioning
confidence: 99%
“…Omega-3 fatty acid was previously reported to modulate the levels of adiponectin, leptin and adiponectin/leptin ratio. Serum adiponectin levels significantly increased following 8-week of 3 g/d of omega-3 fatty acid supplementation in healthy young female [29]. Also, an increased dietary consumption of fish was found to be associated with a reduced level of leptin [28].…”
Section: Discussionmentioning
confidence: 99%
“…Some of these nutrients includeomega-3 fatty acid [21,22], protein [23], sucrose [24], and dietary [22,25], or foods such as vegetables and fruits [26], whole grain [27], fish [28,29], and legumes [30]. However, other studies showed no association between some dietary component [s] such as vitamins and minerals with adipokine levels [31][32][33].…”
Section: Introductionmentioning
confidence: 99%